Upaya Meningkatkan Kesadaran dan Partisipasi Masyarakat Melalui Kegiatan Donor Darah Di Lingkungan Masjid Imanuddin Graha Raya Bintaro - Hartati, Leni; Sutomo, Sutomo; Reza, Bobby (Jurnal Pemberdayaan Nusantara, 2024)
This Blood Donation Activity aims to increase public awareness and participation in blood donation in the Imanuddin Mosque environment, Graha Raya Bintaro. Blood donation is a form of humanitarian action that can help save lives and support blood needs in health facilities. The implementation of this activity involves various parties, including mosque administrators, community organizations, and health agencies, with a collaborative approach to ensure the sustainability and effectiveness of the program. This activity was carried out on August 31, 2024, involving more than 98 participants who participated as donors. The results of this activity showed the high enthusiasm of the community in supporting the blood donation program, which can be seen from the increase in the number of donors compared to previous activities. In addition, this activity also provides education about the importance of regular blood donation, so that it is expected to become a sustainable program in the mosque environment. The conclusion of this PKM is the importance of the active role of the community in blood donation activities, as well as the need for collaboration between various parties to achieve the success of the activity.